2017
DOI: 10.4172/2329-891x.1000249
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes (Diptera: Culicidae) in Tunisia, with Particular Attention to Proven and Potential Vectors: A Review

Abstract: The state of knowledge of mosquitoes (Diptera: Culicidae) is dispersed and disorganized in Tunisia although their important role as disease vectors. The available published and unpublished reports were collected and reviewed. There are about 43 species of mosquitoes in Tunisia. There are a total of 12 species of Anopheles. The species involved in malaria transmission in Tunisia during the endemic period and still persisting in Tunisia are Anopheles (An.) labranchiae, predominant species in the north and center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent changes in the epidemiological situation of RVF have often been linked to the increasing density in sheep and cattle, animal mobility, intensification of the livestock trade and climatic factors [ 41 ]. Previous studies in Tunisia revealed ubiquitous distribution of Culex and Aedes species [ 42 ]. Other studies demonstrated the RVF competence of Culex pipiens tested using ZH548 and Clone 13 viral strains under laboratory conditions and reported a transmission infection rate of 14.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent changes in the epidemiological situation of RVF have often been linked to the increasing density in sheep and cattle, animal mobility, intensification of the livestock trade and climatic factors [ 41 ]. Previous studies in Tunisia revealed ubiquitous distribution of Culex and Aedes species [ 42 ]. Other studies demonstrated the RVF competence of Culex pipiens tested using ZH548 and Clone 13 viral strains under laboratory conditions and reported a transmission infection rate of 14.7%.…”
Section: Discussionmentioning
confidence: 99%